2019
DOI: 10.1111/jsr.12864
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sleep duration and cognitive impairment in mild cognitive impairment

Abstract: Summary The prevalence of mild cognitive impairment (MCI) increases among elderly people and is associated with a high risk of dementia. Identifying factors that may contribute to the progress of MCI to dementia is critical. The objective of this study was to examine the association of objective sleep with cognitive performance in MCI patients. A subsample of 271 participants with a diagnosis of probable Alzheimer's disease (AD; N = 50) or mild cognitive impairment (MCI; N = 121) and 100 persons who were not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 58 publications
3
44
0
Order By: Relevance
“…A study based on objective actigraphic sleep found a U-shape association between sleep duration and all-cause mortality among elderly [ 66 ]. Several studies have reported associations between long sleep duration and cardiovascular disease, coronary heart disease, cognitive decline, and all-cause mortality in this age group [ 43 , 67 , 68 , 69 , 70 ]. It appears that objective long sleep is a result/marker of increased inflammation in elderly subjects [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study based on objective actigraphic sleep found a U-shape association between sleep duration and all-cause mortality among elderly [ 66 ]. Several studies have reported associations between long sleep duration and cardiovascular disease, coronary heart disease, cognitive decline, and all-cause mortality in this age group [ 43 , 67 , 68 , 69 , 70 ]. It appears that objective long sleep is a result/marker of increased inflammation in elderly subjects [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that adopting a diet rich in vegetables and a physically active lifestyle, by lowering inflammation, could help reduce mortality and morbidity, including cognitive decline among elderly. Furthermore, given that long sleep seems to relate with inflammation levels, as well as cognition and disease severity among elders with cognitive decline [ 42 , 43 , 86 ], we and others have previously reported that treatment with sedative/sleep-prolonging psychotropic medication in this population should be given with caution [ 42 , 43 , 86 , 87 ]. These simple practical recommendations could be easily applied in a primary care setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently from our results, some of them have associated longer sleep times with reduced cognitive performance. 3,20 The use of a subjective sleep assessment could explain the lower sleep duration shown by our MCI-MD participants. One study found that people with MCI reported shorter sleep times and worse sleep quality when compared with data obtained by objective methods.…”
Section: Discussionmentioning
confidence: 95%
“…Differently from our results, some of them have associated longer sleep times with reduced cognitive performance. 3 , 20 …”
Section: Discussionmentioning
confidence: 99%